Drivers of Tourist Satisfaction and Revisit Intention at Selecta Recreation Park - Any Urwatul Wusko; Afiifah Nuur Kharisma (Global Review of Tourism and Social Sciences, 2025)
This study examines the determinants of tourist satisfaction and revisit intention by integrating destination image, social media marketing, and customer experience as key influencing factors. Employing a quantitative explanatory design, data were collected from 120 visitors to Selecta Recreation Park in Batu City, Indonesia, who had visited at least once. The data were analyzed using Partial Least Squares Structural Equation Modeling (SmartPLS 4). The results indicate that destination image and customer experience exert positive and significant effects on satisfaction and revisit intention. Social media marketing, although not significantly associated with satisfaction, positively influences revisit intention. Satisfaction itself has a significant mediating effect on revisit intention, reinforcing its central role in maintaining tourist loyalty. The findings suggest that enhancing the quality of on-site experiences and strengthening the perceived image of the destination are crucial strategies for increasing visitor retention. Conversely, social media marketing should align more closely with the actual visitor experience to avoid expectation gaps. This research contributes to tourism behavior literature by providing empirical evidence on how cognitive and experiential factors jointly shape satisfaction and revisit intention in competitive tourism settings.